Conceptual framework of the active ageing policies in employment in the Czech Republic - Lucie Vidovićová (Center for Social and Economic Research (CASE), 2014)
In this paper the author presents a general assessment of the labour market situation of older workers in the Czech Republic, starting with a more general overview of the demographic situation and emphasizing the generational differences among the young-old and older cohorts, underlying a number of different problems as well as solutions. Further in the paper she addresses the impact of the recent economic situation on employment levels, showing that the recovery in terms of employment has not yet begun and that the impact on older workers is (at least) two-fold: firstly, for older workers it is very difficult to find a new job once unemployed; secondly, if employed, the pressure on workability and the increasing demands of workplaces may be harder to bear for the older the worker. She describes a National Action Plan Supporting Positive Ageing (2013-2017) and other examples of good and transferable praxes which address some of the active ageing issues in an innovative way. The second part of this report examines the issues of employability, workability and age-management as perceived by some of the key actors. The report goes into greater detail on the topic of paid work after retirement, which is considered an important part of the Czech economy, despite the fact that the employment of sizable groups of older workers after retirement is undeclared. Self-entrepreneurship and independent work in later life are another realm of employment that is increasing in importance in the Czech economy; however, as consulted experts argue, it is not to be taken as an unproblematic solution to late-life careers. In the last chapter the author turns her attention to the lifelong learning of older workers and to their up-skilling/retraining. In the concluding remarks, she reemphasizes the need to address the heterogeneity of the older workforce, in the sense of age/generational affiliation, health, socio-economic and other characteristics.
Keywords: H55; H75; M12; M50; 330; Older workers; Labour market; Lifelong learning; Active ageing; Good practice; Czech Republic; Paid work after retirement; Self-entrepreneurship; Trade unions; Focus groups